Treatment of Acute Urinary Tract Infection in Children with Pipemidic Acid - Lydia Kosnadi; Rochmanadji Widayat; Dwi Wastoro; Ari Yunanto; Ristitiati Gunawan (Paediatrica Indonesiana, 1989)
Urinary tract infection in children is still an important problem in uronephrology. The disease.tends to develop recurrently and results in chronic progressive renal disease in the future. Pipemidic acid is a bactericidal quinolone derivate, with a wide spectrum against gram positive and negative bacteria. Compared with nalidixic acid, pipemidic acid proves to be more effective against Pseudomonas, E. coli, Alkali genes and Salmonella. Thirty one cases with acute urinary tract infection had been studied descriptively. The etiology revealed as follows: E. coli (45.2%), Alkaligenes (16.2%), Enterobacter (9.6%), Staphylococcus (9.6%), Pseudomonas (9.6%), Paracolon (6,5%), and Proteus (3.3%). Pipemidic acid was administered orally to these patients, 15-20 mg/kg/day divided in 2 equal doses for 10 days. Bacteriological examinations was repeated on the 6th day and 11th day treatment. The result revealed that on the 6th day of treatment, in 27 patients (87, 09%) there was no bacteriuria while on the 11th day the urine of 29 patients (93.54%) were sterile. In conclusion, a 5 day treatment of acute urinary tract infection in children with pipemidic acid is quite effective.